A Sociedade Pós-Industrial e a Possível Recepção do Pool of Risks: aprimoramento e gestão do risco ambiental pelo ordenamento jurídico pátrio - Sarturi, Vinícius Gustavo (Universidade do Vale do Rio dos Sinos, 2017)
This dissertation comprises the analysis of the characteristics of the postindustrial society, marked by globalization and a visible distance from the legal rules applicable to the actual needs of the contemporary period, based on mass industrialization, technological development and proliferation of risk on a large and complex scale. It also analyzes the economic, political and institutional crisis that destroys public authorities and prevents, at a national level, the adoption of measures capable of implementing an adequate management of the environmental risk, envisaging in the theoretical formation of the pool of risks, from the theory created by Gunther Teubner, addressed in this dissertation in eminently descriptive, the possibility of implementing an effective preventive management model. In this context, the fundamentals underlying this theoretical formation are presented, which are based on the creation of conglomerates of entrepreneurs whose activities are capable of generating environmental damages, in previously delimited territorial bases, with special focus on the individualization of ecological risk areas and on the possibility of joint liability of this conglomerate, in the event of any damage being brought about in previously individualized territories. The fact that in the pool of risks joint liability occurs even when there is no causal relationship between the damage and the actual responsible for its consummation gains prominence, being possible in such circumstances to penalize any of the members of the pool, concluding on the feasibility of this new systematization be received by the legal structures in force, with innovative potential that has the conditions to promote relevant measures of control by the country's law, which may reduce the incidence of disasters in national territory.
Keywords: Sociedade pós-industrial; Pool of risks; Direito ambiental; Solidariedade; Nexo de causalidade; Causalidade jurídica; Sociedade de risco; Vulnerabilidade; Desastres ambientais; Post-industrial society; Pool of risks; Environmental law; Joint liability; Chain of causation; Legal causation; Society of risk; Vulnerability; Environmental disasters; ACCNPQ::Ciências Sociais Aplicadas::Direito